KEANEKARAGAMAN JENIS-JENIS ANGGREK KEPULAUAN KARIMUNJAWA - Sulistiarini, Diah; Djarwaningsih, Tutie (Jurnal Teknologi Lingkungan, 2009)
Karimunjawa is a group of small islands which is situated at 0 up to 506 above sealevels, and covered of total forests area of about 1,300 ha. The area is locatedwithin Jepara Regency, Central Java. Studies on forest ecology and floristic ofthe island has been conducted in 2003 to 2006. The present study is apart of thefloristic studies with special attention to orchids. Based on field study combinedwith specimen herbarium stored in the Herbarium Bogoriense, there are at list 13species of orchid collected from Karimunjawa Island, and one of them is recognizedas endemic species in Jawa. In addition there is one unidentified species which isbelonging to genus Eria.